Recovery minyak jelantah menggunakan antioksidan alami kulit buah manggis - Endang Tri Wahyuni Maharani; Mohammad Rizky Febriansyah; Dewi Rokhmatul Adhimah; Diode Yonata (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Repeated cooking oil (used cooking oil) can cause the lubricant to smoke or foam when frying and leave a brown color. One of the factors that influences oil damage is the auto-oxidation process. The reactions during the auto-oxidation process in oil will form peroxide compounds. To reduce the peroxide value in used cooking oil, a substance is needed that prevents oxidation, namely an antioxidant. This research aimed to determine the antioxidant effect of mangosteen peel powder on the peroxide value and acid value of used cooking oil. The study used a non-factorial wholly randomized design. The research results obtained showed that mangosteen peel powder contained an antioxidant activity of 36.97% RSA, and the addition of mangosteen peel powder significantly reduced the peroxide value and acid value of used cooking oil. In conclusion, the addition of 12% mangosteen peel powder was able to improve the quality of used cooking oil by reducing the peroxide value (7.02 to 4.39 mg O2/100g) and acid value (1.08 to 0.73 mg KOH/g)